Outcomes of dexmedetomidine versus propofol sedation in critically ill adults requiring mechanical ventilation: a systematic review and meta-analysis of randomised controlled trials. (October 2022) - Heybati, Kiyan; Zhou, Fangwen; Ali, Saif; Deng, Jiawen; Mohananey, Divyanshu; Villablanca, Pedro; Ramakrishna, Harish
Abstract: Background: Guidelines have recommended the use of dexmedetomidine or propofol for sedation after cardiac surgery, and propofol monotherapy for other patients. Further outcome data are required for these drugs. Methods: This systematic review and meta-analysis was prospectively registered on PROSPERO. The primary outcome was ICU length of stay. Secondary outcomes included duration of mechanical ventilation, ICU delirium, all-cause mortality, and haemodynamic effects. Intensive care patients were analysed separately as cardiac surgical, medical/noncardiac surgical, those with sepsis, and patients in neurocritical care. Subgroup analyses based on age and dosage were conducted. Results: Forty-one trials ( N =3948) were included. Dexmedetomidine did not significantly affect ICU length of stay across any ICU patient subtype when compared with propofol, but it reduced the duration of mechanical ventilation (mean difference −0.67 h; 95% confidence interval: −1.31 to −0.03 h; P =0.041; low certainty) and the risk of ICU delirium (risk ratio 0.49; 95% confidence interval: 0.29–0.87; P =0.019; high certainty) across cardiac surgical patients. Dexmedetomidine was also associated with a greater risk of bradycardia across a variety of ICU patients. Subgroup analyses revealed that age might affect the incidence of haemodynamic side-effects and mortality among cardiac surgical and medical/other surgical patients. Conclusion: Dexmedetomidine did not significantly impact ICU length of stay compared with propofol, but it significantly reduced the duration of mechanical ventilation and the risk of delirium in cardiac surgical patients. It also significantly increased the risk of bradycardia across ICU patient subsets.